2020
DOI: 10.1155/2020/2425401
|View full text |Cite
|
Sign up to set email alerts
|

Game-Theoretic Models of Green Products in a Two-Echelon Dual-Channel Supply Chain under Government Subsidies

Abstract: This paper deals with issues concerning green subsidies of government and optimal decisions of a manufacture and dual-channel retailers in a two-echelon dual-channel supply chain. Both a decentralized supply chain and a centralized supply chain are considered. Sufficient and necessary conditions for guaranteeing that the two supply chains run normally under government subsidies are proposed. For the decentralized supply chain, a three-layer model is constructed according to different priorities of the four par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Thirdly, δ > θ is widely adopted when involving different products or dual channels [15]- [16]. This setting suggests that the impact brought by one's own price is always greater than the impact brought by another product's price.…”
Section: Assumption and Notationsmentioning
confidence: 99%
“…Thirdly, δ > θ is widely adopted when involving different products or dual channels [15]- [16]. This setting suggests that the impact brought by one's own price is always greater than the impact brought by another product's price.…”
Section: Assumption and Notationsmentioning
confidence: 99%
“…Li et al [20] studied a dynamic price game model in a dual-channel green supply chain considering firm's innovation input of green products and channel service. Lou et al [21] explored the issues concerning green subsidies of government and optimal decisions of a manufacture and dual-channel retailers in a two-echelon dual-channel supply chain. e above literature works mainly discuss the pricing for the dual channel, but the uncertainty of the online channel is not considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e following equations are derived based on equations (21) to (23). Data Availability e data used to support the findings of this study are included within the article.…”
Section: G Proofs Of Propositions 6-9mentioning
confidence: 99%
“…Regarding the quality of new energy products, Liu and Xia (2020) used the evolutionary game model to analyze the impact factors of strategic selection between customers and manufacturers. Lou et al (2020) developed game-theoretic models of green products in a two-echelon dual-channel supply chain under government subsidies. Zhao N. et al (2020) analyzed the subsidy-related deception behavior in energy-saving products based on the game theory and indicated that government regulation is necessary to keep manufacturers honest.…”
Section: Regulation Game For Different Productsmentioning
confidence: 99%